Design & development of instrumentation for the experiments on cell-material interaction of the surface of biodegradable metals - Siti Hanisah Zainuddin, 1989-, author; Hendra Hermawan, supervisor; Fakulti Biosains Dan Kejuruteraan Perubatan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda Kejuruteraan (Bio - Perubatan)) - Universiti Teknologi Malaysia, 2013